Determination of antioxidant activity of dehydrozingerone through hydroxy radical scavengers using deoxyribosa method - Agung Endro Nugroho; Nunung Yuniarti; Enade Perdana Estyastono; Supardjan .; Lukman Hakim (Indonesian Journal of Pharmacy, 2006)
Dehydrozingerone (4-(4-hydroxy-3-methoxyphenyl)-3-buten-2-one) is an analog of curcumin which is termed as half-curcumin. The compound is isolated from ginger (Zingiber officinale). Nevertheless, this compound still has a phenolic hydroxy moiety responsible for antioxidant activity. The research was performed to obtain information on the antioxidant activity of dehydrozingerone through hydroxy radical scavengers.The study was performed according to a hydroxy radical scavenging procedur. In this method, reaction between hydroxy radical, resulted from phenton reaction, and deoxyribosa produces malonedealdehyde. Incubation in thiobarbituric acid at low pH produced violet-coloured solution (complex MDA-TBA).The results showed that dehydrozingerone has antioxidant activity through hydroxy radical scavengers with ES15 value of 48.36 μM. The antioxidant activity of dehydrozingerone was lower than curcumin, with ES15 value of 25.01 μM. Besides, exchange of phenolic hydroxy moiety by salting with potassium could deplete its antioxidant activity. Based on these facts, it can be concluded that phenolic hydroxy moiety of dehydrozingerone was important for its antioxidant activity through hydroxy radical scavengers.Key words : dehydrozingerone, curcumin, antioxidant, radical hydroxy, Zingiber